El derecho internacional privado y el derecho comunitario - Abelardo Posso Serrano (Ius Humani. Jornal do direito, 2010)
Private international law is justified at a time when the legal systems of nation states seeking a way to extend their areas and competencies. This desire led to the conflict between national laws, which grew smaller as did the novel concept of "international community", but did not suppress national relativism. A new law began to settle, then, with the progress of the integration process. Community laws have mechanisms to be applied, even when states would try to ignore them or to fulfill a relative way.